Use of Methadone for Neuropathic Pain - Dwight Moulin (Pain Research and Management)
Chronic neuropathic pain is often considered to be a common complication of injury to the central or peripheral nervous system and the pain itself is usually assumed to be intractable. Both of these assumptions are inaccurate. For example, numbness and tingling in glove and stocking distribution are common accompaniments of longstanding diabetes mellitus, but only about 10% of patients with diabetic neuropathy consider these sensory changes to be painful (1). Anticonvulsant and antidepressant treatments provide effective analgesia in up to 50% of patients with chronic neuropathic pain (2) and there is a growing body of high-quality evidence that controlled-release opioid analgesics provide substantial pain relief in a further subset of patients (3-6). Even with polypharmacy, this still leaves perhaps 20% to 30% of chronic neuropathic pain sufferers lacking adequate analgesia, and side effects can be problematic. In addition, central pain appears to be more refractory to opioid treatment than pain due to peripheral nerve injury (7).